“Mini sambutan kayuhan 25 tahun UiTM Cawangan Pulau Pinang” program in conjunction with the 25th anniversary celebration of UiTM - Wahid, Norlizan; Bahari, Khairil Anuar; Lahap@Wahab, Johanudin; Che Ani, Adi Izhar (Unit Penerbitan PKAPP, 2025)
The “Mini Sambutan Kayuhan 25 Tahun UiTM Cawangan Pulau Pinang” program was held on 29 June 2024. The UiTM Penang cycling team, together with support crews led by Ts. Dr. Adi Izhar Che Ani, joined the main team of the “Kayuhan Kapsul Rentas Cawangan Sempena 25 Tahun UiTM” program on a 169.05 km journey from UiTM Pulau Pinang, Permatang Pauh Campus, to UiTM Perak, Seri Iskandar Campus. The program was organized to demonstrate support for the main team of the “Kayuhan Kapsul Rentas Cawangan Sempena 25 Tahun UiTM,” which commenced its cross-campus journey across Peninsular Malaysia on 20 June 2024. This commemorative ride celebrates the 25th anniversary of UiTM’s establishment as a public institution of higher learning, officially founded on 26 August 1999. The cycling program involved a total of 30 participants, including cyclists and support staff. Among them were 12 staff cyclists, including the sole female rider, Norlizan Wahid, a lecturer from Pengajian Kejuruteraan Awam, UiTM Pulau Pinang, and 4 student cyclists. They have cycled nearly 2,000 km across Peninsular Malaysia in a two-week period starting from 20 June to 2 July 2024.